2008
DOI: 10.1016/j.ydbio.2008.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Nkx genes regulate heart tube extension and exert differential effects on ventricular and atrial cell number

Abstract: Heart formation is a complex morphogenetic process, and perturbations in cardiac morphogenesis lead to congenital heart disease. NKX2-5 is a key causative gene associated with cardiac birth defects, presumably because of its essential roles during the early steps of cardiogenesis. Previous studies in model organisms implicate NKX2-5 homologs in numerous processes, including cardiac progenitor specification, progenitor proliferation, and chamber morphogenesis. By inhibiting function of the zebrafish NKX2-5 homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
90
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 50 publications
10
90
1
Order By: Relevance
“…Our previous studies in zebrafish have revealed roles for nkx2.5 and nkx2.7 in limiting atrial cell number and promoting ventricular cell number (Targoff et al, 2008). Here, through characterization of a newly identified nkx2.5 mutation, we find that loss of nkx2.5 function causes formation of a voluminous atrial chamber and a miniscule ventricular chamber despite normal specification of chamber-specific precursor populations.…”
Section: ;Hand2mentioning
confidence: 58%
See 4 more Smart Citations
“…Our previous studies in zebrafish have revealed roles for nkx2.5 and nkx2.7 in limiting atrial cell number and promoting ventricular cell number (Targoff et al, 2008). Here, through characterization of a newly identified nkx2.5 mutation, we find that loss of nkx2.5 function causes formation of a voluminous atrial chamber and a miniscule ventricular chamber despite normal specification of chamber-specific precursor populations.…”
Section: ;Hand2mentioning
confidence: 58%
“…Embryos were injected at the one-cell stage with 2 ng of an anti-nkx2.7 morpholino (MO) (5Ј-TGGAGGTCACAGGACTCGGAAGCAT-3Ј) (Targoff et al, 2008) along with 2 ng of an anti-p53 (tp53 -Zebrafish Information Network) MO (5Ј-GCGCCATTGCTTTGCAAGAATTG-3Ј) (Robu et al, 2007). For mosaic cell-labeling experiments, embryos were injected at the one-cell stage with 150 pg of Tg(myl7:EGFP) plasmid.…”
Section: Injectionmentioning
confidence: 99%
See 3 more Smart Citations